Migration, skill, and the transformation of social networks in the pre‐Hispanic Southwest. Issue 2 (7th June 2016) - Mills, Barbara J.; Clark, Jeffery J.; Peeples, Matthew A.
Abstract: Migration restructures interaction at different social and spatial scales and has the potential to create deep and lasting inequalities between migrants and hosts. But migrants may also create relationships that mediate inequalities and assume positions of power. We examine how migration restructured social relationships in the late pre‐Hispanic U.S. Southwest and argue that skilled migrant potters were responsible for both technological innovation and the success of migrants in their new homes. The Southwest has well‐documented examples of a diaspora from northeastern Arizona to destinations to the south. Using social network analyses conducted by the Southwest Social Networks Project, we investigate the position of migrant settlements vis‐à‐vis their hosts. Migration transformed social networks fromad 1200 to 1450 as newcomers became increasingly central by maintaining relationships through bonds of shared heritage and creating social positions for themselves within host communities. Comparison of early and late periods shows how migrants were initially weakly tied to their hosts, which led to stronger ties in a significant portion of the Southwest. These ties indicate widespread interactions characteristic of a social movement. Skilled migrants innovated the production of ceramics that became highly valued in their respective destinations, showing how technological transformations, migration, and skill intersected.